Verborgen, unsichtbar, unlesbar - zur Problematik restringierter Schriftpräsenz - Krüger, Kristina (Materiale Textkulturen, 2014)
From the perspective of early modernity, the presence of writing is linked to its visibility and legibility. This may be a questionable assumption, and it was especially problematic for writers in the premodern era, for whom concealment and veiling played such an important role. The aim of this book is to critically examine the category of the "restricted presence of writing," from an interdisciplinary and transcultural perspective.